Myoglobin Expression in Chelonia mydas Brain, Heart and Liver Tissues - RINI PUSPITANINGRUM; SEPTELIA INAWATI WANANDI; RONDANG ROEMIATI SOEGIANTO; MOHAMAD SADIKIN; DARYL ROBERT WILLIAMS; ANDREW ROBERT COSSINS (Bogor Agricultural University, Indonesia, 2010)
An understanding of the underpinning physiology and biochemistry of animals is essential to properly understand the impact of anthropogenic changes and natural catastrophes upon the conservation of endangered species. An observation on the tissue location of the key respiratory protein, myoglobin, now opens up new opportunities for understanding how hypoxia tolerance impacts on diving lifestyle in turtles. The respiratory protein, myoglobin has functions other than oxygen binding which are involved in hypoxia tolerance, including metabolism of reactive oxygen species and of the vascular function by metabolism of nitric oxide. Our work aims to determine whether myoglobin expression in the green turtle exists in multiple non muscle tissues and to confirm the hypothesis that reptiles also have a distributed myoglobin expression which is linked to the hypoxiatolerant trait. This initial work in turtle hatch Chelonia mydas confirms the presence of myoglobin transcriptin brain, heart and liver tissues. Furthermore, it will serve as a tool for completing the sequence and generating an in situ hybridization probe for verifying of cell location in expressing tissues.